The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1126/science.1142210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aneuploidy on Cellular Physiology and Cell Division in Haploid Yeast

Abstract: Aneuploidy is a condition frequently found in tumor cells, but its effect on cellular physiology is not known. We have characterized one aspect of aneuploidy: the gain of extra chromosomes. We created a collection of haploid yeast strains that each bear an extra copy of one or more of almost all of the yeast chromosomes. Their characterization revealed that aneuploid strains share a number of phenotypes, including defects in cell cycle progression, increased glucose uptake, and increased sensitivity to conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

94
1,309
5
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 848 publications
(1,438 citation statements)
references
References 28 publications
94
1,309
5
3
Order By: Relevance
“…To investigate a causative relationship between aneuploidy and aging, we measured the replicative lifespans (RLS) of a set of previously well‐characterized disomic yeast strains (‘disomes’): haploid cells, each carrying an extra copy of one of 13 of 16 native yeast chromosomes (Table S1) (Torres et al ., 2007, 2010; Sheltzer et al ., 2011; Oromendia et al ., 2012; Dephoure et al ., 2014). We determined the RLS for each disome using the gold standard method of manually separating daughter cells as they bud from a single mother cell and counting the number of buds produced before a mother cell ceases to divide (Steffen et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate a causative relationship between aneuploidy and aging, we measured the replicative lifespans (RLS) of a set of previously well‐characterized disomic yeast strains (‘disomes’): haploid cells, each carrying an extra copy of one of 13 of 16 native yeast chromosomes (Table S1) (Torres et al ., 2007, 2010; Sheltzer et al ., 2011; Oromendia et al ., 2012; Dephoure et al ., 2014). We determined the RLS for each disome using the gold standard method of manually separating daughter cells as they bud from a single mother cell and counting the number of buds produced before a mother cell ceases to divide (Steffen et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…These YACs are similar in size to native yeast chromosomes but due to the different genetic density of mammalian genomes compared to S. cerevisiae , and the lack of appropriate splicing machinery in yeast, many fewer transcripts and proteins are likely expressed from YACs. Furthermore, previous comparisons between these disomes and YAC strains showed that the YAC strains did not suffer from the proteotoxic stress commonly experienced by disomes (Torres et al ., 2007, 2010; Oromendia et al ., 2012; Dephoure et al ., 2014). Similarly, we found that while the disomes were short lived, strains carrying YACs even as large as 1.6 megabases had lifespans that were similar to wild‐type (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations